Effect on Temporal Response Adjustable Parameter Adaptive Control with Reference Model First Order - Vargas Tamani, Bruno (2014)
Experimental results are presented adaptive control with reference model of a plant according to your previously made identification can be represented as a first order system. Is chosen as the reference model also one of the first order with unity gain. Adaptive controller analysis is performed, justifying its performance in closed loop depends on the proper choice of a scale parameter adjustable. The controller is implemented and temporary plant responses to step inputs for different kinds of adjustable parameter values are recorded.